2022
DOI: 10.4236/ojas.2022.123035
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality of Meat from Cattle Breed in Livestock Production Area of Cameroon

Abstract: In Cameroon, foods of animal origin are an important part of the population's diet. To improve meat consumption and assure its safety, the Government plan a project for the industrialization of cattle and pig industries by building a slaughter chain, cold stores and acquiring of vehicles and trucks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…In the study moisture values determined from beef were similar to the values found in other studies (Ngom et al, 2022;Salim et al, 2023;Santana et al, 2023). However, the moisture value in Korean Hanwoo cattle was reported to be lower (69.21%) than the determined value (Bostami et al, 2023).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…In the study moisture values determined from beef were similar to the values found in other studies (Ngom et al, 2022;Salim et al, 2023;Santana et al, 2023). However, the moisture value in Korean Hanwoo cattle was reported to be lower (69.21%) than the determined value (Bostami et al, 2023).…”
Section: Resultssupporting
confidence: 87%
“…The protein values found for cattle in the study were similar to some of the values found in the researches (Hamed Hammad Mohammed et al, 2020;Pouzo et al, 2023;Santana et al, 2023), higher than some (Salim et al, 2023) and lower than some (Oliveira et al, 2021;Ngom et al, 2022). While the values reported for sheep were in agreement with (Costa et al, 2009;Romero-Bernal et al, 2017;Radzik-rant et al, 2023) or higher than literature reports and findings (Mioč et al, 2007;Lima et al, 2022;Latoch et al, 2023;Lunesu et al, 2023;Uushona et al, 2023).…”
Section: Figure 2 Ash Content Of Meat Samples Obtained From Different...supporting
confidence: 88%
See 2 more Smart Citations
“…[18]. Tese animals serve as sources of food, which are an essential part of the diet of the Cameroonian population [30]. Brucellosis is more of a disease of cattle than any other animals [2].…”
Section: Discussionmentioning
confidence: 99%